Principles of genetics - Snustad Peter D Simmons Michael J (John Wiley & Sons, 2003)
Since the last edition, the science of genetics has passed a major milestone: The DNA sequence of the human genome has been determined. This edition has been prepared with the new issues, questions, insights, and technologies in mind. Recent discoveries have been incorporated into the text, and the pedagogy has been enhanced, balancing new information with fundamental principles.